Karakteristik Penggunaan Smartphone (Gadget) Pada Balita Usia 1 – 5 Tahun Di Desa Dukuhmaja Kecamatan Songgom Kabupaten Brebes - Bella Al Kurniati; Umi Solikhah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To determine the characteristics of the use of smartphones (gadgets) in infants aged 1-5 years in the Dukuh Maja village, Songgom, Brebes.Method: This type of research is descriptive. The population in this study were toddlers aged 1-5 years in Dukuh Maja village as many as 418. The sample in this study was 81 respondents with a sampling technique that is cluster random sampling.Results: The results showed that the characteristics of the use of smartphones (gadgets) which include frequency in the medium category were 63 respondents (77.8%), the duration of the majority in the moderate category were 61 respondents (75.3%), egocentric behavior had a good category of 53 respondents (65.4%), the majority of emotional behavior in the good category were 43 respondents (53.1%), social interaction had a good category of 56 respondents (69.1%), the type of content had a good category of 52 respondents (64, 2%).Conclusion: The use of smartphones (gadgets) in infants in the medium category, but should be a concern for all parents of their children.Keywords: Characteristics, smartphone, toddlers